Postinduction turnoff of beta-interferon gene expression. - Whittemore, L A (1990)
Viral induction of the human beta-interferon (IFN-beta) gene leads to a transient accumulation of high levels of IFN-beta mRNA. Previous studies have shown that the increase in IFN-beta mRNA levels after induction is due to an increase in the rate of IFN-beta gene transcription. In this paper, we show that the rapid postinduction decrease in the level of IFN-beta mRNA is due to a combination of transcriptional repression and rapid turnover of the mRNA. This transcriptional repression can be blocked with cycloheximide, suggesting that the synthesis of a virus-inducible repressor is necessary for the postinduction turnoff of the IFN-beta gene. Analysis of the sequence requirements for IFN-beta mRNA instability revealed two regions capable of destabilizing a heterologous mRNA. One destabilizer is an AU-rich sequence in the 3' untranslated region, and the other is located 5' to the translation stop codon.